Neutrophil and Monocyte Function in Patients with Chronic Hepatitis C Undergoing Antiviral Therapy with Regimens Containing Protease Inhibitors with and without Interferon - Gambato, Martina (PLoS One, 2016)
Real-life data showed an increased incidence of bacterial infections in patients with advanced liver disease receiving a protease inhibitor (PI)-containing antiviral regimen against hepatitis C (HCV). However, the causes of this event are unknown. We hypothesized that PIs might impair innate immune responses through the inhibition of proteases participating in the anti-bacterial functions of neutrophils and monocytes. The aims of the study were to assess phagocytic and oxidative burst capacity in neutrophils and monocytes obtained from patients receiving a PI containing-antiviral regimen, and to determine cytokine secretion after neutrophil stimulation with flagellin. Forty patients with chronic HCV (80% with cirrhosis) were enrolled in the study, 28 received triple therapy (Group A) with pegylated-interferon and ribavirin for 4 weeks followed by the addition of a PI (telaprevir, boceprevir or simeprevir), and 12 patients received an interferon-free regimen (Group B) with simeprevir and sofosbuvir. Phagocytosis and oxidative burst capacity were analyzed by flow cytometry at baseline, week 4, and week 8 of therapy. In neutrophils from Group A patients, oxidative burst rate and oxidative enzymatic activity per cell significantly decreased throughout the study period (p = 0.014 and p = 0.010, respectively). Pairwise comparisons showed a decrease between baseline and week 4 and 8 of therapy. No differences were observed after the introduction of the PI. The oxidative enzymatic activity per cell in monocytes significantly decrease during the study period (p = 0.042) due to a decrease from baseline to week 8 of therapy (p = 0.037) in patients from Group A. None of these findings were observed in Group B patients. Cytokine secretion did not significantly change during the study in both groups. In conclusion, our data suggest that the use interferon (rather than the PI) has a deleterious effect on neutrophil and monocyte phagocytic and oxidative burst capacity in this cohort of patients with HCV-related advanced liver fibrosis.